Continuing education and professional development of library staff involved with makerspaces. Issue 4 (18th November 2019) - Horton, Jennifer
Abstract : Purpose: This paper reports the results of a survey of library staff members working with a library makerspace or with makerspace-related technologies. The purpose of this paper is to identify who is working with library makerspaces, what methods of training they have used, what training methods they prefer, and what topics they would like to see included in professional development and continuing education. Design/methodology/approach: A 17-question survey was posted to two library makerspace-related listservs for two weeks. Findings: The survey results found a varied array of job title of individuals working with library makerspaces. It also identified the preferred training methods, as well as the varied topics requested for professional development, showing a large need for a makerspace training in library staff. Originality/value: This is the first study conducted about the preferred methods and topics of professional development and continuing education of library staff members working with makerspaces or makerspace-related technologies.